Análisis del impacto de los créditos otorgados por distintos organismos a las PYMES, sector panadería del cantón Quevedo 2011 - 2012. - Albarado Cano, María Ana (2015)
In Quevedo city, there is a large number of PYMES focused on the bakery sector, which stimulate the economy of the city, but it is known that for successful development of a company must have a source of funding to boost growth and development, and that source in many cases is a financial institution. PYMES entrepreneurs show that they don´t have sufficient support from financial institutions, because they don´t receive the information and don´t get all requirements to apply and which sometimes do not have that hinder the access to credit. The main objective of this research is to analyze the impact of loans to PYMES bakeries from Quevedo, 2011 - 2012, the percentage of PYMES bakery had accessed to bank financing was determined, it was explained the financing sources and cost-benefit provided that credit to the business, must determine in a qualitative way, because these businesses do not maintain accounts of their activities to measure the impact. In order to meet the objectives of this research were interviewed entrepreneurs from PYME sector bakery recorded by FENAPAN and 15 financial institutions that work in Quevedo city, applying a series of questions, plus direct observation of those involved were surveyed within their business helped to obtain the necessary information. As another important point the impact of loans identified to achieve the development of PYMES bakeries from Quevedo and found that these loans granted by financial institutions to PYMES industry bakeries from Quevedo do not cover the needs of the PYMES, therefore do not contribute to economic development.